The Effect of Product Knowledge, Promotion and Reputation on Intention to Use Islamic Banking Products - Ardita Zahrani, Fani; Amalia, Alvien Nur (Jurnal Ilmu Manajemen dan Ekonomika, 2024)
This study aims to examine the relationship and the extent of the influence of product knowledge, promotion, and reputation on the intention to use Islamic banking products following the merger of Bank Syariah Indonesia (BSI). The study employs a quantitative approach, using questionnaires and multiple linear regression analysis techniques. The population consists of both customers and non-customers of Bank Syariah Indonesia (BSI), with a sample of 125 respondents from the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) area. The findings indicate that the three variables—product knowledge, promotion, and reputation—positively influence the intention to use Islamic banking products, whether tested individually or collectively. Among the three independent variables, promotion has the greatest influence, followed by product knowledge and reputation. These results are expected to inform the management of Bank Syariah Indonesia (BSI) in making decisions aimed at increasing its customer base and to serve as a reference for future research.